Zonation of The Waters of Spermonde Archipelago Base on Nutrient Concentration and Its Impact to Coral Reef Ecosystem - Faizal, Ahmad (Hasanuddin University, 2023)
The Spermonde Archipelago is divided into four zones, the division of zones is based on the distribution of coral reefs, distance from the mainland, and water depth, but this condition tends to change as a result of high anthropogenic activity in the Spermonde Islands. Based on this, it is very necessary to re-zoning the Spermonde Archipelago Waters based on the condition of nutrient distribution. The research method uses the integration of remote sensing data analysis, field surveys, and secondary data which are then analyzed using the Boleean method for re-zoning. The results showed that the nutrient, in this case, chlorophyll-a, was concentrated in the deep zone (near the mainland) and the concentration was higher during the rainy season, this condition affected the coral reef cover in the Spermonde Islands. Based on these conditions, the Spermonde Islands waters are divided into three zones, namely the inner zone with high nutrient conditions with a benthic cover dominated by fleshy macroalgae, the middle zone with low nutrient conditions with crustose coralline dominance, and the outer zone with low nutrient conditions with algal turf dominance turf alga/corals.